2018
DOI: 10.12659/msm.909183
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Rehabilitation on Fatigue Level in Patients with Multiple Sclerosis

Abstract: BackgroundThe objective of this study was to evaluate the effect of a rehabilitation program in changing the perception of fatigue in patients with multiple sclerosis.Material/MethodsThe study involved 65 respondents/patients with clinically confirmed multiple sclerosis (54 women, 11 men, average age 46.49 years). The evaluation of the effects of fatigue on the physical, psychological, and psychosocial aspects of life was assessed using the Modified Fatigue Impact Scale (MFIS). To test the effectiveness of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 31 publications
(44 reference statements)
2
8
0
1
Order By: Relevance
“…The improvements seen in the 2MWT (+17m) and TUG (‒2.1 s) exceed the reported minimum for clinically meaningful changes for the 2MWT (+9.1 m) [ 37 ] and the TUG (‒0.75 s) [ 38 ] and are in the range of other rehabilitation studies in MS reporting improvements of 14.8 m (35.1%) [ 13 ] for the 2MWT and ‒1.2 s (‒7.9%) for the TUG [ 39 ]. The improvement in fatigue (FSMC) by ‒6 points (‒9.4%) at the 3-month follow-up is in line with other studies, which showed a decrease in fatigue levels after rehabilitation [ 40 ] of ‒6.1 points (‒12.4%) evaluated with the Modified Fatigue Impact Scale. However, the 6 points (95% CI 2‒11) improvement in fatigue on the FSMC 3 months after rehabilitation compared with 1 week before rehabilitation in the current study is below the reported minimum for a clinical meaningful change of 9 points (95% CI ‒6.8‒11.2) reported by Svenningsson et al [ 41 ].…”
Section: Discussionsupporting
confidence: 89%
“…The improvements seen in the 2MWT (+17m) and TUG (‒2.1 s) exceed the reported minimum for clinically meaningful changes for the 2MWT (+9.1 m) [ 37 ] and the TUG (‒0.75 s) [ 38 ] and are in the range of other rehabilitation studies in MS reporting improvements of 14.8 m (35.1%) [ 13 ] for the 2MWT and ‒1.2 s (‒7.9%) for the TUG [ 39 ]. The improvement in fatigue (FSMC) by ‒6 points (‒9.4%) at the 3-month follow-up is in line with other studies, which showed a decrease in fatigue levels after rehabilitation [ 40 ] of ‒6.1 points (‒12.4%) evaluated with the Modified Fatigue Impact Scale. However, the 6 points (95% CI 2‒11) improvement in fatigue on the FSMC 3 months after rehabilitation compared with 1 week before rehabilitation in the current study is below the reported minimum for a clinical meaningful change of 9 points (95% CI ‒6.8‒11.2) reported by Svenningsson et al [ 41 ].…”
Section: Discussionsupporting
confidence: 89%
“…Study by Michel cava et al conducted to investigate effect of rehabilitating treatments on fatigue in patients with MS; showed that complementary methods such as rehabilitating plans is effective in reducing fatigue in patients with MS (Mikulakova, Klimova, Kendrova, Gajdos, & Chmelik, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Another frequent symptom reported by MS patients is fatigue, which is encountered in 75–95% of cases [ 133 , 134 , 135 ] and is considered a key factor affecting the quality of life in these people [ 136 , 137 ]. Fatigue is defined as a perceived reduction in physical and mental energy that hinders everyday activities [ 135 ].…”
Section: Present Therapeutic Approachesmentioning
confidence: 99%
“…Another frequent symptom reported by MS patients is fatigue, which is encountered in 75–95% of cases [ 133 , 134 , 135 ] and is considered a key factor affecting the quality of life in these people [ 136 , 137 ]. Fatigue is defined as a perceived reduction in physical and mental energy that hinders everyday activities [ 135 ]. Physical exercise, especially aerobic training, can improve both primary and secondary fatigue in MS patients, through direct changes in the central nervous system and inflammation reduction, but also by improving depression symptoms and quality of sleep [ 138 ].…”
Section: Present Therapeutic Approachesmentioning
confidence: 99%